Efektivitas Evaluasi Pembelajaran dalam Menghadapi Akreditasi Sekolah - Baharuddin, Cut Nirawati (El-Idare, 2024)
: The problem of this research is the lack of maximumity in the learning evaluation process carried out by teachers at MTsN 7 Aceh Timur. This research aims to determine the effectiveness of learning evaluation in improving the quality of learning in facing madrasa accreditation. The research method used is qualitative research with descriptive survey techniques. The results of the research show that the evaluation implementation process has not run optimally. It can be seen that there are still teachers who do not evaluate students after learning takes place. The evaluation implementation at MTsN 7 Aceh Timur uses formative assessments, mid-semester exams (UTS), end-of-year assessments (PAS). After carrying out the evaluation stage, there were students who had not completed their learning so corrections were carried out, but what happened was that the students did not care about the evaluation results obtained and did not come when asked to take part in the remedial. The research implications are strategies for increasing teacher competency, improving the quality of assessment, curriculum development and learning methods.